UNVEILING THE ESSENCE OF EUROPEAN ISLAM: A Critical Analysis of Abdennour Bidar's Concepts of Self Islam and Islamic Existentialism - Agus Riwanda; Abd A’la (IAIN Ponorogo, 2023)
This article discusses the challenges of European Islam at the intersection of Islamic traditions and modern liberal democratic values and the urgency of bridging the two. European Islam is looking for a common ground that can combine reason and faith in harmony, integrate the values of modernity with the spiritual view of Islam, and identify the challenges and opportunities faced by European Islam in the context of Western liberal society. Bidar, in his contribution to the concept of European Islam, argues that religion is not only about rituals but also about profound spiritual experiences. He proposed the concept of Self Islam, which emphasizes individual freedom, personal responsibility, and spiritual connection with Allah. According to Bidar, individual freedom is the key to spiritual life. In addition, everyone can choose how to practice religion according to his spiritual needs. Bidar proposed Islamic reform, oriented towards the unification of religions and modernity, by prioritizing humanist values and human rights and reforming Islam in the light of modernity. According to him, humans become God's autonomous vicegerent on earth and have the right to manage it freely but responsibly. In addition, in harmony with Kantian, Bidar believes that human immortality can be achieved through piety and good deeds. According to him, humans become God's autonomous vicegerent on earth and have the right to manage it freely but responsibly. In addition, in harmony with Kantian, Bidar believes that human immortality can be achieved through piety and good deeds. According to him, humans become God's autonomous vicegerent on earth and have the right to manage it freely but responsibly. In addition, in harmony with Kantian, Bidar believes that human immortality can be achieved through piety and good deeds.